Symptoms of common mental disorders in professional football (soccer) across five european countries - Gouttebarge, V.; Backx, F. J. G.; Aoki, H.; Kerkhoffs, G. M. (Journal of Sports Science & Medicine, 2015)
Evidence on the prevalence of symptoms related to distress, anxiety/depression or substance abuse/dependence, - typically referred to as symptoms of common mental disorders (CMD) - is lacking in European professional football (soccer). The aims of the present study were to investigate the prevalence of symptoms related to CMD (distress, anxiety/depression, sleeping disturbance, adverse alcohol behaviour, and adverse nutrition behaviour) in professional footballers from five European countries, and to explore associations of the outcome measures under study with life events and career dissatisfaction. A cross-sectional design was used. Questionnaires were distributed among professional footballers by the national players` unions in Finland, France, Norway, Spain and Sweden. The highest prevalence of symptoms related to common mental disorders were 18% for distress (Sweden), 43% for anxiety/depression (Norway), 33% for sleeping disturbance (Spain), 17% for adverse alcohol behaviour (Finland), and 74% for adverse nutrition behaviour (Norway). In Finland, France and Sweden, both life events and career dissatisfaction were associated with distress, anxiety/depression, adverse alcohol behaviour, and adverse nutrition behaviour. Results suggest the need for self-awareness in professional football about common mental disorders and a multidisciplinary approach by the medical team.